Superparasitism by Palmistichus elaeisis (Hymenoptera: Eulophidae) and defense behaviors of two hosts - ALVARENGA-SOARES, MARCUS; TORRES-GUTIERREZ, CAROLINA; COLA-ZANUNCIO, JOSÉ; RODRIGUES PORTO PEDROSA, ALINE; SIMÕES LORENZON, ALEXANDRE (Revista Colombiana de Entomología, 2009)
Several families of parasitoids are capable of discriminating among parasitized and unparasitized hosts. However, some cases of superparasitism have been recorded in species of Eulophidae. The objective of this study was to investigate whether females of Palmistichus elaeisis (Eulophidae) superparasitize pupae of Thyrinteina arnobia (Lepidoptera: Geometridae) and Hylesia sp. (Lepidoptera: Saturniidae) in the laboratory and to describe the defense mechanisms of those hosts. The experiment was done in the insectary of the Universidade Federal de Viçosa, Brazil. Petri dishes were used as oviposition chambers and contained two T. arnobia pupae, one of them parasitized by P. elaeisis and the other not. The pupae were placed on each side of the dish. Petri dishes were likewise set up with two pupae of Hylesia sp. For both treatments, ten females of P. elaeisis were released in the center of the dish, which represented a replicate. A total of eight replicates were used for each treatment. The oviposition preference of P. elaeisis on host pupae was observed for six hours and analyzed using the chi-square test (X2) (P 0.01). In observing the defense behavior of the hosts, T. arnobia pupae showed spinning movements which in turn induced superparasitism in less mobile pupae. Individuals of Hylesia sp. did not show any defense behavior and in this case the discrimination led to a clear choice for the unparasitized pupae.